Covalent organic framework cross-linked sulfonated polybenzimidazole proton exchange membrane as well as preparation method and application thereof

The sulfonated polybenzimidazole proton exchange membrane crosslinked by covalent organic framework solves the problem of difficult balance of conductivity and ion selectivity in all vanadium flow batteries, improves the cycle stability and energy efficiency of the battery, and reduces the Cost, efficient power storage is achieved.

CN119315067APending Publication Date: 2025-01-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411385155.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

There are problems of positive and negative electrode vanadium ion crossing, capacity attenuation and low energy efficiency in all vanadium flow batteries, mainly because the ion selectivity and conductivity of the membrane materials are difficult to balance, and the cost of commercial Nafion films is high, which limits large-scale use. .

Method used

The sulfonated polybenzimidazole proton exchange membrane with covalent organic framework crosslinking is used to improve hydrophilicity through sulfonation treatment, introduce COF crosslinking agent to increase free volume, build a fast proton transport channel, and improve the conductivity and ions of the membrane. Selectively, reduce conduction resistance.

Benefits of technology

It significantly improves the cycle stability and energy efficiency of all vanadium flow batteries, reduces the intersection of positive and negative electrode active materials, reduces operation and maintenance costs, and provides cost advantages and high safety water-based batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315067A_ABST
    Figure CN119315067A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow batteries, in particular to a covalent organic framework cross-linked sulfonated polybenzimidazole proton exchange membrane as well as a preparation method and application thereof. The proton exchange membrane structurally comprises a polymer main chain, a sulfonic acid group, a connecting agent and a cross-linking agent molecule, a sulfonated polybenzimidazole polymer, a COF cross-linking agent and the connecting agent are dissolved in N-methyl pyrrolidone, and the COF cross-linked sulfonated polybenzimidazole proton exchange membrane is obtained after treatment. Aiming at the problems that vanadium ions of a positive electrode and a negative electrode of an all-vanadium redox flow battery are crossed, the capacity of the all-vanadium redox flow battery fades and the energy efficiency is low, the hydrophilicity of the sulfonated polybenzimidazole proton exchange membrane is improved through sulfonation treatment, and the mass transfer resistance is reduced. After the covalent organic framework is introduced, the increased free volume is beneficial to construction of a rapid proton transmission channel and can accommodate water molecules to limit swelling of the membrane material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of all-vanadium liquid flow batteries, and in particular to a covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane and a preparation method and application thereof. Background Art

[0002] The installed capacity of wind and solar power with storage in my country has been increasing year by year, but renewable energy power generation is intermittent and volatile and cannot be directly integrated into the power grid. Long-term energy storage technology has the advantages of peak load regulation and frequency regulation, so it is urgent to develop long-term energy storage technology that matches renewable energy. It is generally believed that long-term energy storage is an energy storage system with a discharge time of more than 4 hours. Long-term energy storage technologies mainly include: compressed air energy storage, pumped water energy storage, molten salt energy storage and flow batteries. Liquid flow batteries are considered to be the preferred technical route for the development of long-term energy storage technology because of their high energy conversion efficiency, stable and safe, and flexible deployment.

[0003] At present, the most mature liquid flow battery is the all-vanadium liquid flow battery. The positive electrolyte of the all-vanadium liquid flow battery is a solution containing 4-valent vanadium ions and 5-valent vanadium ions, and the negative electrolyte is a solution containing 2-valent vanadium ions and 3-valent vanadium ions. Through the redox reaction of vanadium ions of different valence states at the positive and negative electrodes, the mutual conversion between electrical energy and chemical energy is completed, and the storage and release of electrical energy are realized. As a key material in liquid flow batteries, membrane materials have the functions of preventing the crossover of positive and negative electrolytes, isolating the anode and cathode, and conducting protons. At present, the commercial Nafion membrane is used in all-vanadium liquid flow batteries. Nafion membrane has the advantages of good chemical stability and high conductivity. However, due to its poor ion selectivity, there is a serious crossover of positive and negative vanadium ions during the circulation process of the all-vanadium liquid flow battery, resulting in the bottleneck problems of low coulombic efficiency and capacity attenuation in the all-vanadium liquid flow battery. Moreover, due to the monopoly of science and technology in the United States, the cost of Nafion membrane is expensive, which limits the large-scale use of all-vanadium liquid flow batteries.

[0004] Polybenzimidazole has good ion selectivity in all-vanadium flow batteries due to its protonated amino group and rigid polymer skeleton, and is considered to be a candidate material for proton membranes for all-vanadium flow batteries. However, its poor proton conductivity in aqueous sulfuric acid solution limits its application. Therefore, the development of polybenzimidazole proton exchange membranes with high conductivity and high ion selectivity will hopefully solve the bottleneck problems of low coulombic efficiency and capacity attenuation in all-vanadium flow batteries. Summary of the invention

[0005] In view of the defects of the prior art such as vanadium ion crossover between the positive and negative electrodes of all-vanadium liquid flow batteries, capacity attenuation and low energy efficiency, the purpose of the present invention is to provide a covalently organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane and a preparation method and application thereof, so as to solve the problem of difficulty in balancing conductivity and ion selectivity in the related technology.

[0006] In order to achieve the above objectives, the technical solutions adopted are:

[0007] A covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane, the proton exchange membrane structure comprises a polymer main chain, a sulfonic acid group, a linker and a cross-linker molecule, as shown in formula (I);

[0008]

[0009] Wherein, the polymer main chain is a polybenzimidazole polymer or a derivative thereof.

[0010] The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane, the cross-linking agent molecule comprises a COF cross-linking agent having a structure as shown in formula (II) or (III):

[0011]

[0012] The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane has a structure of a sulfonated benzimidazole proton exchange membrane cross-linked by any one of the COF cross-linking agents (II) and (III).

[0013] The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane, the linker has a structure as shown in formula (IV):

[0014]

[0015] The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane has a proton exchange membrane structure that is a sulfonated benzimidazole proton exchange membrane connected by one or more connecting agents selected from dibromobutane, dibromopentane, dibromohexane, dibromoheptane and dibromooctane.

[0016] The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane has a cross-linking degree of 2% to 45% and an ion exchange capacity of 0.5 to 3.0 meq / g; preferably, the cross-linking degree is 5% to 35%, the sulfonation degree is 30% to 100%, and the ion exchange capacity is 1.0 to 2.8 meq / g.

[0017] The method for preparing the covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane comprises the following steps:

[0018] S1. polymerizing monomer A and 3,3'-diaminobenzidine under polyphosphoric acid catalysis to obtain a polymer backbone;

[0019] S2. The polymer backbone obtained in step S1 is dissolved in concentrated sulfuric acid, treated at a set temperature for a set time, and then taken out, washed with deionized water, and dried to obtain a sulfonated polybenzimidazole polymer;

[0020] S3. The 3,3'-dicyanobipyridine or 2,5-dicyanopyridine is dissolved in trifluoromethanesulfonic acid, treated at a set temperature for a set time, removed and washed with deionized water and dried to obtain a COF crosslinking agent;

[0021] S4. The polymer obtained in step S2, the COF cross-linking agent and the linking agent obtained in step S3 are dissolved in N-methylpyrrolidone and treated at a set temperature for a set time to obtain a COF cross-linked sulfonated polybenzimidazole proton exchange membrane.

[0022] The method for preparing the covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane comprises the following steps: in step S1, the polymerization reaction temperature range is 140°C to 280°C, and the polymerization reaction time is 2h to 24h; in step S2, the treatment temperature range is 60°C to 120°C, and the treatment time is 4h to 24h; in step S3, the treatment temperature range is -10°C to 100°C, and the treatment time is 1h to 3h; in step S4, the treatment temperature range is 50°C to 100°C, and the treatment time is 24h to 96h.

[0023] The application of the covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane is used as a proton exchange membrane of an all-vanadium redox flow battery.

[0024] The application of the covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane, the positive electrode electrolyte of the all-vanadium liquid flow battery is a solution containing tetravalent vanadium ions and pentavalent vanadium ions, the negative electrode electrolyte is a solution containing divalent vanadium ions and trivalent vanadium ions, the supporting electrolyte is one or more of sulfuric acid, hydrochloric acid or phosphoric acid, and the molar concentration ratio of the positive electrode electrolyte to the negative electrode electrolyte is 1:1 to 2:1; the bipolar plate of the all-vanadium liquid flow battery is a graphite bipolar plate, and the current collector of the all-vanadium liquid flow battery is one of carbon cloth and graphite carbon felt.

[0025] The design idea of ​​the present invention is:

[0026] The present invention designs and prepares a covalent organic framework cross-linked (COF) sulfonated polybenzimidazole proton exchange membrane, and improves the hydrophilicity of the polybenzimidazole proton exchange membrane through sulfonation treatment to reduce mass transfer resistance. After the introduction of the covalent organic framework, the increased free volume helps to construct a fast proton transfer channel and can accommodate water molecules to limit the swelling of the membrane material.

[0027] The advantages and beneficial effects brought by the technical solution provided by the present invention are as follows:

[0028] The present invention provides a method for preparing a covalent organic framework (COF) cross-linked proton exchange membrane, thereby obtaining a proton exchange membrane suitable for an all-vanadium redox flow battery, improving the conductivity and ion selectivity of the proton exchange membrane, and improving the cycle stability and energy efficiency of the all-vanadium redox flow battery.

[0029] The proton exchange membrane contains a large number of imidazole and pyridine groups. After protonation under acidic conditions, the positive charge it carries will have a strong repulsive effect on vanadium ions. A large number of sulfonic acid groups can provide conductive active sites for protons and improve proton conductivity. The most important COF cross-linking agent has a large free volume, which can not only limit the water absorption and swelling of the proton exchange membrane, but also significantly reduce the conduction resistance of the proton, and further improve the proton conductivity while ensuring the high ion selectivity of the polybenzimidazole (PBI) membrane. Therefore, the crossover of positive and negative active substances occurring during the operation of the all-vanadium battery can be greatly reduced, and the operation and maintenance cost of the all-vanadium liquid flow battery can be reduced. In addition, the prepared proton exchange membrane is low in cost, stable in chemical properties, can be reused many times, and has obvious cost advantages.

[0030] At the same time, the all-vanadium liquid flow battery is an aqueous battery with extremely high safety. The prepared electrolyte can be recycled for many times and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a performance diagram of the 400-cycle all-vanadium liquid flow battery of Example 1.

[0032] Figure 2 This is the performance diagram of the 200-cycle all-vanadium liquid flow battery of Comparative Example 1. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] In the embodiments of the present invention, all are configured to correspond to flow batteries, and the test parameters and equipment refer to the contents recorded in "NBT 42081-2016 All-vanadium flow battery single cell performance test method", and the test environment and steps are as follows:

[0035] Test environment:

[0036] ——Ambient temperature: 20℃±5℃;

[0037] ——Air humidity: 50%±5%;

[0038] ——Electrolyte temperature: 30℃±5℃.

[0039] Test steps:

[0040] a) The battery system is charged to 90% SOC;

[0041] b) The battery system is operated at a current density of 200 mA / cm 2 Discharging until the discharge cut-off voltage;

[0042] c) The battery system is operated at a current density of 200 mA / cm 2 Charging is performed until the charging cut-off voltage;

[0043] d) The battery system is operated at a current density of 200 mA / cm 2 Discharging until the discharge cut-off voltage;

[0044] e) repeat steps c) to d);

[0045] f) Record various parameters of each charge and discharge cycle;

[0046] g) The average coulombic efficiency, voltage efficiency and energy efficiency of the all-vanadium liquid flow battery are the average values ​​of the data after multiple cycles.

[0047] Example 1

[0048] In this embodiment, a method for preparing a proton exchange membrane for an all-vanadium liquid flow battery is as follows:

[0049] 1. The selected proton exchange membrane is as follows:

[0050]

[0051] 2. The preparation process of proton exchange membrane is as follows:

[0052] S1. Dissolve 4,4'-diphenyl ether dicarboxylic acid and 3,3'-diaminobenzidine in polyphosphoric acid, and stir at 140° C. for 3 h to obtain a viscous polymer as the polymer main chain.

[0053] S2. The polymer main chain obtained in step S1 is dissolved in concentrated sulfuric acid (98 wt%) and stirred at 100° C. for 4 h to obtain a sulfonated polybenzimidazole polymer.

[0054] S3. Dissolve 3,3'-dicyanobipyridine in trifluoromethanesulfonic acid. After the mixture is completely dissolved, heat it at 100°C for 2h to obtain a crosslinker molecule tripyridyl-s-triazine COF.

[0055] S4. The crosslinking agent molecule tripyridyl-s-triazine COF, the linker dibromobutane and the sulfonated polybenzimidazole polymer are dissolved in N-methylpyrrolidone, and stirred at 80° C. for 96 hours to obtain a crosslinked polymer.

[0056] In this embodiment, the thickness of the proton exchange membrane is 55 μm, the micropore diameter of the proton exchange membrane is 0.2 nm, the cross-linking degree of the proton exchange membrane is 24%, the sulfonation degree of the proton exchange membrane is 80%, and the ion exchange capacity of the proton exchange membrane is 1.8 meq / g.

[0057] 3. The configuration of the all-vanadium liquid flow battery is as follows:

[0058] Negative electrode: 1.6 mol / L solution of divalent vanadium ions and trivalent vanadium ions, the balance is water;

[0059] Positive electrode: 1.6 mol / L solution of 4-valent vanadium ions and 5-valent vanadium ions, the balance is water;

[0060] The flow battery is a single cell, in which the bipolar plate is a graphite electrode and the current collector is a graphite carbon felt. The flow battery storage tank uses two 0.1L transparent bottles, and a peristaltic pump is used as a power source between the storage tank and the battery stack. The volume of the negative electrode electrolyte is 0.1L, and the volume of the positive electrode electrolyte is 0.1L.

[0061] Example 2

[0062] The difference from Example 1 is that the selected proton exchange membrane is as follows:

[0063]

[0064] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.

[0065] Example 3

[0066] The difference from Example 1 is that the selected proton exchange membrane is as follows:

[0067]

[0068] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.

[0069] Example 4

[0070] The difference from Example 1 is that the selected proton exchange membrane is as follows:

[0071]

[0072] The preparation of the proton exchange membrane, the configuration of the positive and negative electrolytes, and the configuration of the flow battery are the same as those in Example 1.

[0073] Table 1 Flow battery test table

[0074] Coulombic efficiency % Voltage efficiency % Energy efficiency % Capacity retention rate % Example 1 99.25% 79.92% 79.33% 76.23% Example 2 99.68% 80.18% 79.92% 77.88% Example 3 99.12% 81.32% 79.21% 78.15% Example 4 99.80% 79.56% 78.85% 79.60%

[0075] like Figure 1 As shown, the all-vanadium liquid flow battery of Example 1 was subjected to 400 cycles of charge and discharge cycle test. From the above experiment, it can be seen that the all-vanadium liquid flow battery assembled by the COF cross-linked sulfonated polybenzimidazole proton exchange membrane exhibits good cycle stability and capacity retention rate. The experimental results of Examples 1 to 4 are similar to Figure 1 , the coulombic efficiency is 99.12%~99.80%, the voltage efficiency is 79.56%~81.32%, the energy efficiency is 78.85%~79.92%, and the capacity retention rate is 76.23%~79.60%. From the specific experimental data, it can be seen that the proton exchange membrane battery cross-linked with COF cross-linker with smaller molecular weight has better performance.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that the comparative example is an all-vanadium liquid flow battery, which is configured as follows:

[0078] Membrane material: Nafion212;

[0079] Negative electrode: 1.6 mol / L solution of divalent vanadium ions and trivalent vanadium ions, the remainder is water, the volume is 0.1L.

[0080] Positive electrode: 1.6 mol / L solution of tetravalent vanadium ions and pentavalent vanadium ions, the remainder being water, with a volume of 0.1 L.

[0081] After assembly is completed, the battery cycle performance test is carried out according to the above test conditions. Figure 2 As shown, after 200 cycles of charge and discharge cycle testing, the capacity retention rate of the battery is greatly attenuated, with a decay rate of about 40%, a coulombic efficiency of 95.55%, an energy efficiency of 74.51%, and a voltage efficiency of 77.98%.

[0082] It can be seen from the above experimental results that the COF cross-linked sulfonated polybenzimidazole proton exchange membrane provided by the present invention greatly improves the stability and capacity retention rate of the all-vanadium redox flow battery.

[0083] The implementation results show that the present invention designs and prepares a COF cross-linked sulfonated polybenzimidazole proton exchange membrane, and improves the hydrophilicity of polybenzimidazole by introducing sulfonic acid groups, thereby improving the proton conductivity of the membrane. The increased free volume after the introduction of COF helps to build a fast ion transmission channel and limit the swelling of the polymer membrane. The conductivity of the sulfonated polybenzimidazole proton exchange membrane is improved while ensuring high ion selectivity, inhibiting the crossover of the positive and negative active substances of the all-vanadium liquid flow battery, and improving the capacity attenuation and low energy efficiency of the all-vanadium liquid flow battery. After 400 charge and discharge cycles, the all-vanadium liquid flow battery using this series of proton exchange membranes maintains a high energy efficiency and capacity retention rate, and the long-term cycle stability is improved by 100%.

[0084] The above description of the present invention only provides some specific embodiments for those skilled in the art to facilitate understanding and implementation. For these embodiments, those skilled in the art may make a variety of obvious improvements, and the basic principles defined in the present invention may be applied in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention should not be limited to the embodiments shown in the present invention document, and other changes and modifications to the present invention without departing from the spirit and scope of the present invention should be covered by the claims of the present invention.

Claims

1. A covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane, characterized in that: The proton exchange membrane structure includes a polymer main chain, a sulfonic acid group, a linker and a cross-linker molecule, as shown in formula (I); Wherein, the polymer main chain is a polybenzimidazole polymer or a derivative thereof.

2. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 1, characterized in that: The crosslinker molecule comprises a COF crosslinker having a structure as shown in formula (II) or (III):

3. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 2, characterized in that: The proton exchange membrane structure is a sulfonated benzimidazole proton exchange membrane cross-linked by any one of the COF cross-linking agents (II) and (III).

4. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 1, characterized in that: The linking agent has a structure as shown in formula (IV):

5. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 4, characterized in that: The proton exchange membrane structure is a sulfonated benzimidazole proton exchange membrane connected by one or more connecting agents selected from dibromobutane, dibromopentane, dibromohexane, dibromoheptane and dibromooctane.

6. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 1, characterized in that: The cross-linking degree of the proton exchange membrane is 2% to 45%, and the ion exchange capacity is 0.5 to 3.0 meq / g; preferably, the cross-linking degree is 5% to 35%, the sulfonation degree is 30% to 100%, and the ion exchange capacity is 1.0 to 2.8 meq / g.

7. A method for preparing a covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. polymerizing monomer A and 3,3'-diaminobenzidine under polyphosphoric acid catalysis to obtain a polymer backbone; S2. The polymer backbone obtained in step S1 is dissolved in concentrated sulfuric acid, treated at a set temperature for a set time, and then taken out, washed with deionized water, and dried to obtain a sulfonated polybenzimidazole polymer; S3. The 3,3'-dicyanobipyridine or 2,5-dicyanopyridine is dissolved in trifluoromethanesulfonic acid, treated at a set temperature for a set time, removed and washed with deionized water and dried to obtain a COF crosslinking agent; S4. The polymer obtained in step S2, the COF cross-linking agent and the linking agent obtained in step S3 are dissolved in N-methylpyrrolidone and treated at a set temperature for a set time to obtain a COF cross-linked sulfonated polybenzimidazole proton exchange membrane.

8. The method for preparing a covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 7, characterized in that: In step S1, the polymerization reaction temperature range is 140°C to 280°C, and the polymerization reaction time is 2h to 24h; in step S2, the treatment temperature range is 60°C to 120°C, and the treatment time is 4h to 24h; in step S3, the treatment temperature range is -10°C to 100°C, and the treatment time is 1h to 3h; in step S4, the treatment temperature range is 50°C to 100°C, and the treatment time is 24h to 96h.

9. Use of the covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to any one of claims 1 to 6, characterized in that: The proton exchange membrane is used as a proton exchange membrane of an all-vanadium liquid flow battery.

10. The covalent organic skeleton cross-linked sulfonated polybenzimidazole proton exchange membrane according to claim 9, characterized in that: The positive electrode electrolyte of the all-vanadium liquid flow battery is a solution containing tetravalent vanadium ions and pentavalent vanadium ions, the negative electrode electrolyte is a solution containing divalent vanadium ions and trivalent vanadium ions, the supporting electrolyte is one or more of sulfuric acid, hydrochloric acid or phosphoric acid, and the molar concentration ratio of the positive electrode electrolyte to the negative electrode electrolyte is 1:1 to 2:1; the bipolar plates of the all-vanadium liquid flow battery are graphite bipolar plates, and the current collector of the all-vanadium liquid flow battery is one of carbon cloth and graphite carbon felt.

Citation Information

Cited By

  • Covalent organic framework-polymer hybrid porous membrane as well as preparation method and application thereof

    CN120878879A

  • Polybenzimidazole modified ion conducting membrane for flow battery and preparation method of polybenzimidazole modified ion conducting membrane

    CN121181962A

  • High-oxidation-resistance polybenzimidazole proton exchange membrane as well as preparation method and application thereof

    CN121378746A